STUDENTS’ LEARNING STYLES AND PREFERRED TEACHING STYLES IN PHILIPPINE CLASSROOM - C, Emejidio (International Journal of Psychosocial Rehabilitation, 2020)
This study determines and analyzes foreign students’ learning styles, preferred teaching styles and the challenges they encountered while studying in the Philippines. The study uses Descriptive method to describe the current state of the phenomenon involved in the process. Specifically, Sequential Mixed Approach was utilized to analyze the data through surveys and qualitative interpretation. This study used Purposive sampling to gather respondents based on the purposes of the study, whereas Convenience Sampling was used to choose the respondents according to their availability during the data gathering procedure. The result of the study reveals that most of the respondents are visual learners. Thus, the learning styles have no significant difference when grouped according to profile. Majority of the male respondents preferred Delegator as their preferred teaching style than female. Also, language, teachers, and cultural differences are regarded as the top three challenges of the foreign students while studying in the Philippines. Thus, it is recommended for the foreign students to develop their learning styles and to explore other learning styles so that they may have wide-range knowledge on learning. On the other hand, the teachers may understand that the goal of teaching is learning, therefore, it is suggested that teachers need to cater the differences and the diversity inside the classroom to create a productive learning environment.